Diversity of insect pollinators with reference to their impact on yield production of canola (Brassica napus L.) in Ismailia, Egypt - Kamel, Soliman M.; Mahfouz, Hatem M.; Blal, Abd EL-Fatah H.; Said, Maysa; Mahmoud, Mahmoud Farag (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
A study of insect pollinators and their impact on canola yield was conducted during the 2013/2014 and 2014/2015 growing seasons. The study was carried out at an experimental farm, Faculty of Agriculture, Suez Canal University, Ismailia. The results revealed that 21 species of insect pollinators belonging to 14 families under four orders visited canola flowers. The abundance of Hymenoptera insects reached the maximum of 67.90%, followed by Diptera 14.97%, Coleoptera 13.61%, then Lepidoptera 2.26% as average of both seasons. In open pollination, Colletes lacunatus had the maximum percent abundance in the two seasons (30.45 and 29.34%, respectively) followed by Apis mellifera (12.34 and 17.73%, respectively), compared to other bees and different pollinators. Peaks of foraging activity of both C. lacunatus and A. mellifera were mainly observed from 1:00 to 3:00 pm and they corresponded to the number of flowering plants. Open pollination increased the number of pods per plant, seeds per pod, weight of 1000 seeds, yield per plant, yield per feddan (1 fed = 0.42 ha) and seed germination, compared to non-open pollination.